Dampak Perkembangan New Media Pada Pola Komunikasi Masyarakat - Mubarok Ahmadi (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2020)
The development of New Media has given a tendency to communication patterns of the public in general, this is because the facilities provided by New Media are more than the old media (Old Media), and of course every change has an impact on society in general. Recently the internet as a new media (new media) in the science of communication that is most often used by the community and in the end has led to a new culture. The more real people's freedom in terms of media also has an impact on the increasing quality of social interactions which were previously limited by distance and communication time constraints. . Technological sophistication minimizes and even eliminates these obstacles so as to improve the quality of the communication process that exists between humans. With the presence of new media (New Media) will form a community group called virtual community groups, virtual community groups are very dependent on media and as if the real world is the world. informatics where in the world they can telescope the vast nature, communicate with distant communicants but seem to ignore the communicants around them so that this human individualistic nature is very real. However, with the presence of this New media social transactional theory seems to weaken where openness virtual society is taller, more outspoken. So that with the development of new media as a result of the development of information technology it is able to provide a lot of information to the public, both the good and the bad of these communities depend on each other.